Pengaruh Personal Branding Rachel Vennya Pada Akun Instagram @temanbaik.rachelvennya Terhadap Minat Social Campaign - Savana, Adinda; Irrianda, Jhulianfika (LUGAS Jurnal Komunikasi, 2024)
In an increasingly competitive world, personal branding is not only applicable to celebrities or famous entrepreneurs. Everyone, from professionals to students, can take steps to build their own positive image. Personal branding helps to differentiate oneself from others, strengthen reputation, and influence how others perceive us. This study aims to determine the extent of the influence of Rachel Vennya's Personal Branding on the Instagram account @temanbaik.rachelvennya towards Social Campaign interest. This research uses a quantitative associative research method, using data collection techniques through questionnaires, documentation, and literature study. The results of this study indicate that with a sample of 100 followers, it shows that the Personal Branding variable has a strong and positively patterned relationship with the Social Campaign interest variable. The results of the coefficient of determination testing show that Rachel Vennya's personal branding on the Instagram account @temanbaik.rachelvennya has an influence on social campaign interest.